2017
DOI: 10.18632/oncotarget.17737
|View full text |Cite
|
Sign up to set email alerts
|

The oxido-metabolic driver ATF4 enhances temozolamide chemo-resistance in human gliomas

Abstract: Malignant gliomas are devastating neoplasia with limited curative treatment options. Temozolomide (TMZ, Temcat®, Temodal® or Temodar®) is a first-line treatment for malignant gliomas but the development of drug resistance remains a major concern. Activating transcription factor 4 (ATF4) is a critical oxido-metabolic regulator in gliomas, and its role in the pathogenesis of TMZ-resistance remains elusive. We investigated the effect of TMZ on human glioma cells under conditions of enhanced ATF4 expression (ATF4O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 35 publications
5
44
0
1
Order By: Relevance
“…Correspondingly, it has been shown that ATF4 and NRF2 inhibit ferroptosis at least partly through upregulating SLC7A11 expression, whereas p53 promotes ferroptosis by repressing SLC7A11 expression [ 51 55 ]. In addition, it has been shown that ATF4 and NRF2 promote resistance to various cellular stresses, including oxidative stress, genotoxic stress induced by chemotherapy, and proteasome inhibition, at least partly through SLC7A11 [ 26 , 31 , 56 , 57 ], which is in line with the similar protective functions of SLC7A11 in mediating these stress responses as discussed in the previous section. Recent studies have indicated that NRF2 and ATF4 regulate cancer cell dependency on either glucose or glutamine through SLC7A11.…”
Section: Molecular Regulation Of Slc7a11supporting
confidence: 55%
“…Correspondingly, it has been shown that ATF4 and NRF2 inhibit ferroptosis at least partly through upregulating SLC7A11 expression, whereas p53 promotes ferroptosis by repressing SLC7A11 expression [ 51 55 ]. In addition, it has been shown that ATF4 and NRF2 promote resistance to various cellular stresses, including oxidative stress, genotoxic stress induced by chemotherapy, and proteasome inhibition, at least partly through SLC7A11 [ 26 , 31 , 56 , 57 ], which is in line with the similar protective functions of SLC7A11 in mediating these stress responses as discussed in the previous section. Recent studies have indicated that NRF2 and ATF4 regulate cancer cell dependency on either glucose or glutamine through SLC7A11.…”
Section: Molecular Regulation Of Slc7a11supporting
confidence: 55%
“…B, Cell viability was detected by CCK-8 assay. 32,33 The current study demonstrated that P2X4R knockdown reduced ATF4 expression dependent on BDNF/TrkB signaling and ATF4 overexpression reversed the effects of P2X4R on glioma cell growth and apoptosis. D, Cell death detection ELISA kit was used to detect cells apoptosis.…”
Section: Discussionmentioning
confidence: 54%
“…Glioblastoma cells are known to have variable sensitivity to chemotherapeutic agents and to develop chemoresistance ( 37 40 ). As we used a primary GBM cell line, we first performed a dose–response study to determine IC 50 values for TMZ, carmustine, and cisplatin.…”
Section: Resultsmentioning
confidence: 99%